Inhibition of CC chemokine receptor 1 ameliorates osteoarthritis in mouse by activating PPAR-γ - Hanqing Xu; Sheng Chen; Cheng Meng; Yi He; Xiao-jian Huang; Hong-bo You (BMC, 2024)
Abstract Background Osteoarthritis (OA) is a degenerative joint disease characterized by cartilage destruction and inflammation. CC chemokine receptor 1 (CCR1), a member of the chemokine family and its receptor family, plays a role in the autoimmune response. The impact of BX471, a specific small molecule inhibitor of CCR1, on CCR1 expression in cartilage and its effects on OA remain underexplored. Methods This study used immunohistochemistry (IHC) to assess CCR1 expression in IL-1β-induced mouse chondrocytes and a medial meniscus mouse model of destabilization of the medial meniscus (DMM). Chondrocytes treated with varying concentrations of BX471 for 24 h were subjected to IL-1β (10 ng/ml) treatment. The levels of the aging-related genes P16INK4a and P21CIP1 were analyzed via western blotting, and senescence-associated β-galactosidase (SA-β-gal) activity was measured. The expression levels of inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), aggrecan (AGG), and the transcription factor SOX9 were determined through western blotting and RT‒qPCR. Collagen II, matrix metalloproteinase 13 (MMP13), and peroxisome proliferator-activated receptor (PPAR)-γ expression was analyzed via western blot, RT‒qPCR, and immunofluorescence. The impact of BX471 on inflammatory metabolism-related proteins under PPAR-γ inhibition conditions (using GW-9662) was examined through western blotting. The expression of MAPK signaling pathway-related molecules was assessed through western blotting. In vivo, various concentrations of BX471 or an equivalent medium were injected into DMM model joints. Cartilage destruction was evaluated through Safranin O/Fast green and hematoxylin-eosin (H&E) staining. Results This study revealed that inhibiting CCR1 mitigates IL-1β-induced aging, downregulates the expression of iNOS, COX-2, and MMP13, and alleviates the IL-1β-induced decrease in anabolic indices. Mechanistically, the MAPK signaling pathway and PPAR-γ may be involved in inhibiting the protective effect of CCR1 on chondrocytes. In vivo, BX471 protected cartilage in a DMM model. Conclusion This study demonstrated the expression of CCR1 in chondrocytes. Inhibiting CCR1 reduced the inflammatory response, alleviated cartilage aging, and retarded degeneration through the MAPK signaling pathway and PPAR-γ, suggesting its potential therapeutic value for OA. Graphical Abstract